Psammomatoid juvenile ossifying fibroma of mandible in a 6-year-old child - Manjunatha, B. S. (Indian J Dent, 2016)
Juvenile ossifying fibroma (JOF) is a rare fibro-osseous lesion of the jaw occurs at the early age of onset frequently under 15 years with a propensity to recur. It appears as a unilobulated/multilobulated lesion at an early stage followed by radiopaque appearance surrounded by radiolucent rimming at advanced stages. The psammomatous type of JOF (PsJOF) principally involves the bones of the orbit and paranasal sinuses. However in some cases, maxilla or rarely the mandible may be pretentious. Here, we report a challenging case of PsJOF in a 6-year-old child with a complaint of swelling imitating a cystic lesion in left back region of the lower jaw for 2 months. The authors propose that a careful examination and correlations of clinical, radiological, and histopathological features are essential to arrive at correct diagnosis and play a vital role in management of such patients.